The four horsemen of power at the bargaining table. Issue 4 (2nd May 2017) - Galinsky, Adam D.; Schaerer, Michael; Magee, Joe C.
Abstract : Purpose: This paper aims to identify and discuss four major sources of power in negotiations. Findings: The four sources of power are alternatives, information, status and social capital. Each of these sources of power can enhance a negotiator's likelihood of obtaining their ideal outcome because power allows negotiators to be more confident and proactive, and it shields them from the bargaining tactics of their opponents. Practical implications: The paper discusses how negotiators can utilize each source of power to improve their negotiation outcomes. Originality/value: The paper provides a parsimonious definition of power in negotiations, identifies the four major sources of negotiator powers and highlights two pathways by which power affects negotiation outcomes.